Circulating microparticles in patients with antiphospholipid antibodies: Characterization and associations. Issue 1 (January 2015) - Chaturvedi, Shruti; Cockrell, Erin; Espinola, Ricardo; Hsi, Linda; Fulton, Stacey; Khan, Mohammad; Li, Liang; Fonseca, Fabio; Kundu, Suman; McCrae, Keith R.
Abstract The antiphospholipid syndrome is characterized by venous or arterial thrombosis and/or recurrent fetal loss in the presence of circulating antiphospholipid antibodies. These antibodies cause activation of endothelial and other cell types leading to the release of microparticles with procoagulant and pro-inflammatory properties. The aims of this study were to characterize the levels of endothelial cell, monocyte or platelet derived, and tissue factor-bearing microparticles in patients with antiphospholipid antibodies, to determine the association of circulating microparticles with anticardiolipin and anti-β2-glycoprotein antibodies, and to define the cellular origin of microparticles that express tissue factor. Microparticle content within citrated blood from 47 patients with antiphospholipid antibodies and 144 healthy controls was analyzed within 2 hours of venipuncture. Levels of Annexin-V, CD105 and CD144 (endothelial derived), CD41 (platelet derived) and tissue factor positive microparticles were significantly higher in patients than controls. Though levels of CD14 (monocyte-derived) microparticles in patient plasma were not significantly increased, increased levels of CD14 and tissue factor positive microparticles were observed in patients. Levels of microparticles that stained for CD105 and CD144 showed a positive correlation with IgG (R = 0.60, p = 0.006) and IgM anti-beta2-glycoprotein I antibodies (R = 0.58, p = 0.006). The elevation of endothelial and platelet derived microparticles in patients with antiphospholipid antibodies and their correlation with anti-β2-glycoprotein I antibodies suggests a chronic state of vascular cell activation in these individuals and an important role for β2-glycoprotein I in development of the pro-thrombotic state associated with antiphospholipid antibodies.